(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
In general, incarceration is the state of being jailed. In the broader sense, an individual is incarcerated as a punishment and reformation for the commission of offenses that become detrimental to the lives of the member of society. At present, jail management has many rehabilitation and reformation programs being implemented. These programs can efficiently work if the persons deprived of liberty (PDLs) have been trained behaviorally to accept such programs positively. The acceptance of the person to such training andbehavioral reformation can only take place if, despite the stressful jail environment, the PDL has a stable behavioral orientation and a positively inclined personality. The researchers aimed to identify the effects of incarceration on PDLs in Valenzuela City Jail. The researchers utilized descriptive research. It can only be used to create a causal relationship, where one variable affects the other. Descriptive research has an essential requirement for internal validity. The researchers utilized the following instruments to gather the needed data on this particular research. The researchers first used the questionnaire method as the instrument of data collection. The second instrument was an interview; an oral interview was done to gain more knowledge, especially on the respondents, and emphasize the factors involved. The third instrument was focus group discussion. The researchers also used books, magazines, newspapers, Internet sources, and previous theses to develop the concept and contents of the study.The respondents were described according to different demographic profiles. A total of 40% of the respondents were from the age range of 42−50 years old. A total of 100% of the respondents were male, 100% were married, and 60% are M.A. graduates. The respondents agreed that the effects of incarceration that lead to reformation in terms of skill development, job creation, and lifestyle were regarded as extremely effective. The problems encountered that affect the effect of incarceration that led to reformation was regarded as less serious by the respondents. The results of the study can be used as an invitation to investors coming from the business sectors to promote livelihood programs to all PDLs for their total reformation while serving their sentences.